Developmental outcomes of Japanese children born through Assisted Reproductive Technology (ART) in toddlerhood1. Issue 5 (27th February 2018) - Aoki, Sayaka; Hashimoto, Keiji; Ogawa, Kohei; Horikawa, Reiko; Sago, Haruhiko
Abstract: Aim: This study aimed to investigate developmental outcomes of Japanese babies born through Assisted Reproductive Technology (ART) at ages 2 and 3. Methods: The data were gathered from 1085 children in a hospital‐based cohort study conducted in Japan. The children's level of development was assessed through a parent‐rated questionnaire, the Kinder Infant Development Scale, which consists of nine developmental domains. We compared the development of children born through ART and those born naturally by conducting analyses of covariance. For the analyses, the effect of maternal age, family income, parental education and multiple birth were controlled for. Results: At 24 months, no significant difference was found between children born through ART and those born naturally in development in any domain. At 36 months, a significant difference was found in development of Receptive language ( F (1, 845) = 6.148, P = 0.013), Expressive language ( F (1, 845) = 4.060, P = 0.044) and Language concept ( F (1, 845) = 6.968, P = 0.008). For these domains, children born through ART had a significantly higher developmental age compared to children born naturally. Conclusion: At age 2, no significant difference was found between the children born through ART and those born naturally in nine developmental domains, although at age 3, the children born through ART showed significantly better language development than the children born naturally.